2015
DOI: 10.1007/s10811-015-0580-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors on egg liberation and germling production of Sargassum muticum

Abstract: Sargassum muticum is a successful invasive Phaeophyte macroalga, which has colonized from Norway to the Mediterranean in Europe and from Alaska to the Bay of Mexico on the American Atlantic coast. It is also being evaluated as a commercial crop within its native range, SE Asia. Understanding its reproductive tolerance will improve our understanding of its invasive potential and allow optimal germling production for commercial cultivation. Egg liberation, fertilization and germling production were monitored in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
4
10
1
Order By: Relevance
“…Effect of salinity The optimum salinity for the regeneration of receptacles from vesicles and tertiary leaves in the present study was 30-40 psu, which is in agreement with earlier reports for S. swartzii (Sukumaran and Kaliaperumal 2000), S. muticum (Steen 2004;Kerrison and Le 2016), S. ilicifolium (Subbarangaiah et al 2012), and S. vulgare (Appa Rao et al 2014). According to these studies, highest egg fertilization and egg release are observed at 30 and 40 psu salinity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Effect of salinity The optimum salinity for the regeneration of receptacles from vesicles and tertiary leaves in the present study was 30-40 psu, which is in agreement with earlier reports for S. swartzii (Sukumaran and Kaliaperumal 2000), S. muticum (Steen 2004;Kerrison and Le 2016), S. ilicifolium (Subbarangaiah et al 2012), and S. vulgare (Appa Rao et al 2014). According to these studies, highest egg fertilization and egg release are observed at 30 and 40 psu salinity.…”
Section: Discussionsupporting
confidence: 92%
“…s w a r t z i i w a s o p t i m a l a t 4 5 μ m o l photons m −2 s −1 . Similar results have been reported in S. thunbergii in China (Zhao et al 2008) and S. muticum in Scotland (Kerrison and Le 2016). This optimal irradiance is lower than that reported for S. muticum by Hales and Fletcher (1990) (175 μmol photons m −2 s −1 ) and by Cao et al (2008) (60-100 μmol photons m −2 s −1 ), and higher than reported for S. ilicifolium by Appa Rao et al (2014) (9 μmol photons m −2 s −1 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations